2007
DOI: 10.1002/ajim.20461
|View full text |Cite
|
Sign up to set email alerts
|

Daily computer usage correlated with undergraduate students' musculoskeletal symptoms

Abstract: These data suggest a potential dose-response relationship between daily computer usage time and musculoskeletal symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
3
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 21 publications
(32 reference statements)
4
50
3
1
Order By: Relevance
“…Similar to Chang et al [7], we found generally increasing odds ratios for increasing hours of computer use using this classification of exposure. However, we also found a statistically significant association with experiencing any symptoms after 1-2 h of computer use compared to no use.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Similar to Chang et al [7], we found generally increasing odds ratios for increasing hours of computer use using this classification of exposure. However, we also found a statistically significant association with experiencing any symptoms after 1-2 h of computer use compared to no use.…”
Section: Discussionsupporting
confidence: 89%
“…Break length was classified as none, less than 15 min, 15-45 min, and more than 45 min. In order to compare with previous work, a set of indicator variables was created to estimate the association between symptoms and 1-2, 3-5, 6-8 and 9-14 h of computer use compared to no computer use [7].…”
Section: Predictor Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…This prevalence rate is in general agreement with the prevalence rates reported in the literature for college students which vary between 32.9% and 89.3% [6][7][8][9][10][11][13][14][15][16]18,19 . It is however higher than the 32.9% 8 and 36.9% 9 reported among nursing students in Japan, and lower than the 73.3% 18 and 80.0% 19 reported among nursing students in Korea and Australia respectively, as well as the reported prevalence among nurses at the workplace (i.e 78-84.4%) [30][31][32][33] .…”
Section: African Health Sciences Vol 15 Issue 2 June 2015supporting
confidence: 90%
“…They are a major cause of severe long-term pain and disability 1,2 , productivity loss 3 and reduced quality of life 4,5 which can lead to reduced educational attainment among students. In recent years, MSDs have emerged as a public health problem among college students, with the estimated prevalence rate varying between 32.9% and 89.3% in different parts of the world [6][7][8][9][10][11][12][13][14][15][16][17][18][19] . Factors such as computer usage [10][11][12][13]17 , female sex 6,7,14,17 , lack of regular exercise 13,18 and psychosocial stress and mental pressure 6,15 have been associated with increased prevalence of MSDs among this population.…”
Section: Introductionmentioning
confidence: 99%